1994
DOI: 10.1002/elan.1140061003
|View full text |Cite
|
Sign up to set email alerts
|

New amperometric dehydrogenase electrodes based on electrocatalytic NADH‐oxidation at poly (methylene blue)‐modified electrodes

Abstract: Poly(methy1ene blue) (PMBI-modified electrodes show excellent properties for the electrocatal>ric oxidation of NADH concerning the optimal working potential of 0 to 100 my (vs. SCE) and their operation stability. By means of deh!.drogenases entrapped within a Nafion film on top of the PMB layer. new amperometric biosensors for glucose, lactate, malate, and ethanol could be obtained with improved integration of the enzyme and the electrocatalyst directly on the electrode surface. Coentrapment of the negatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(67 citation statements)
references
References 31 publications
1
66
0
Order By: Relevance
“…Methylene blue was extensively used as mediator in a NADdependent dehydrogenase biosensor, since it is known to have good electrocatalytic properties with respect to NADH oxidation [6,7]. A sensor for haemoglobin based on poly(methylene blue) (PMB) electrodeposited on glassy carbon has also been reported [8].…”
Section: E-mail Address: Brett@ciucpt (Cma Brett)mentioning
confidence: 99%
“…Methylene blue was extensively used as mediator in a NADdependent dehydrogenase biosensor, since it is known to have good electrocatalytic properties with respect to NADH oxidation [6,7]. A sensor for haemoglobin based on poly(methylene blue) (PMB) electrodeposited on glassy carbon has also been reported [8].…”
Section: E-mail Address: Brett@ciucpt (Cma Brett)mentioning
confidence: 99%
“…This paper investigates the unique ability of mitochondria on the bioanode to attenuate their ability to oxidize the pyruvate substrate/fuel and produce current in the presence or absence of nitroaromatic explosives. Although bioelectrocatalysis has been considered for a number of biological substrate sensors (i.e glucose, 5 ethanol, 6 hydrogen peroxide 7 ), this is the first use of intact and viable mitochondria rather than individual enzymes of the mitochondria or complete microbial cells for bioelectrocatalysis in sensors. The mitochondria bioelectrocatalysis allows for the investigation of unique attenuation mechanisms that are not present with enzyme systems.…”
mentioning
confidence: 99%
“…Karyakin and coworkers reported that the long-term operational stability of a poly(methylene blue) film was much higher than that of the adsorbed mediator (Karyakin et al 1994). Electropolymerization yields modified electrodes with a three-dimensional distribution of mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Dehydrogenases entrapped in a Nafion® film were deposited on top of a poly(methylene blue)-modified electrode to construct biosensors for glucose, lactate, malate, and ethanol (Karyakin et al 1994). It was shown that the polymerized mediator can be used to oxidize NADH in a comparable way to soluble methylene blue.…”
Section: Electropolymerization Of Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation